Monoamine oxidase A inhibition by toxic concentrations of metaxalone. (3rd May 2020) - Cherrington, Brett; Englich, Ulrich; Niruntari, Supa; Grant, William; Hodgman, Michael
Abstract: Context: Serotonin toxicity is a reported complication associated with both therapeutic use and overdose of metaxalone while on therapeutic doses of serotonergic drugs such as serotonin reuptake inhibitors. Monoamine oxidase A (MAO-A) inhibition by metaxalone has been proposed as the etiology of this toxicity. Metaxalone concentrations reported with cases of serotonin toxicity range from 31 to 61 mcg/ml (140–276 µM). We investigated the effect of metaxalone on MAO-A activity using an in vitro model. Methods: Metaxalone at concentrations ranging from 1.56 to 400 µM were incubated with a proprietary MAO substrate and recombinant human MAO-A for 1 h. After that, an esterase and luciferase were added and luminescence measured. Clorgyline, a known MAO-A inhibitor, was used as a positive control. Luminescence was measured using a Biotek Synergy HT microplate reader. Results: Metaxalone demonstrated significant dose-related inhibition of MAO-A activity. Four-parameter logistic regression analysis demonstrated a strong dose-response relationship at increasing concentrations. Conclusions: Our in vitro model shows that at toxic concentrations similar to those reported in case reports metaxalone shows significant MAO-A inhibition. Clinicians should be aware of this mechanism and understand the potentially lethal interactions metaxalone can have when prescribed with other serotonergic drugs and consider this as a potential cause of serotonin toxicity, especially in overdose scenarios.